Quantum-chemical modeling of excited states of Bismuth monocations - Romanov, A.N.; Kondakova, O.A.; Sulimov, V.B.; Sulimov, A.V.; Oferkin, I.V.; Golovacheva, A.Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
Inorganic dyes are proposed as perspective materials for the dye-sensitized solar cell design. The active media doped with Bismuth represent one possibility of such materials. The open shell atomic structure of Bismuth compounds can cause the broad optical absorption bands in visible and effective solar energy conversion in the whole spectral range. In order to study this possibility, the quantum-chemical simulation of Bismuth monocations is performed for the free ion and for an ion with crystal surrounding. The effect of crystal lattice distortion on the spectral characteristics of monocations is discussed. It is shown that the position of the Bismuth monocation excited states corresponds to the absorption lines in Vis- and NIR-spectral ranges. The breaking of monocation surrounding symmetry by the crystal lattice distortion leads to an additional broadening of Bismuth monocation optical absorption bands.